Basophil allergen threshold sensitivity and component‐resolved diagnostics improve hazelnut allergy diagnosis. Issue 9 (September 2015) - Brandström, J.; Nopp, A.; Johansson, S. G. O.; Lilja, G.; Sundqvist, A.‐C.; Borres, M. P.; Nilsson, C.
Summary Background IgE sensitization to hazelnut is common, especially in birch endemic areas. However, its clinical significance often needs to be confirmed by a food challenge. Objective To evaluate the clinical significance of IgE antibodies to hazelnut components and basophil allergen threshold sensitivity (CD‐sens) to hazelnut, in relation to double‐blind placebo‐controlled food challenge (DBPCFC) in children with a suspected hazelnut allergy. Methods Forty children underwent a DBPCFC. CD‐sens to hazelnut as well as IgE antibodies to hazelnut and its components Cor a 1, Cor a 8, Cor a 9 and Cor a 14 were analysed. Serum tryptase was measured before, during and after DBPCFC. Results Eight children had a positive DBPCFC, and all of them had a high CD‐sens value to hazelnut. Of the 32 children that passed the DBPCFC, 31 were very low or negative in CD‐sens. A positive DBPCFC corresponded with significantly higher CD‐sens values (median 8.9, range 3.3–281) compared to children negative in challenge (median 0.05, range 0–34.7, P < 0.0001). Children positive in challenge also had higher levels of IgE‐ab to Cor a 9 and Cor a 14 (P < 0.01 and P < 0.001, respectively) compared with those with a negative challenge. In relation to the results from DBPCFC, the sensitivity of CD‐sens and IgE‐ab to Cor a 14 was excellent (100%) and the specificity was very high (> 97% and > 94%, respectively). Five of the eight patients positive at challenge showed an increase in tryptase > 20% compared to tryptase baseline levels. Conclusions and Clinical Relevance CD‐sens and component‐resolved diagnostics to hazelnut, used separately or in combination, may improve the diagnostic accuracy and safety and reduce overdiagnosis of hazelnut allergy.